Intensive Reflection in Teacher Training: What is it Good For? - Ene, Estela; Riddlebarger, Cassidy (Journal of Academic Writing, 2015)
The merits of reflective exercises in teacher training are well known. Reflection through journals, surveys/questionnaires, action research, or supervised teaching and classroom discussion creates opportunities for teachers in training to think critically of what they do in their classes, why they do it, and how they could improve. Sometimes, however, teacher training programs may not be ideally positioned to offer novice student teachers (NSTs) the most extensive and coordinated opportunities for teaching, observation, and reflection. The current study examines the usefulness of an intensive reflective exercise realized as a two-question questionnaire used in a Second Language Writing (SLW) course. The findings indicate that the questionnaire was useful in eliciting a fair amount of critical thinking and integration of prior knowledge, new content, and personal experience. For the teacher trainer, it worked as a tool for assessing student learning and planning lessons. The study reflects on the limitations of the intensive reflection exercise applied in it (such as brevity and isolation from other assignments), and makes pedagogical recommendations for future implementation.